Abdominal Skin Rash After TACE Due to Non‐Target Embolization of Hepatic Falciform Artery. Issue 3 (April 2016) - Nagpal, Prashant; Bhalala, Mitesh; Vidholia, Aditi; Sao, Rahul; Sharma, Nisha; Mehta, Dhruv; McCabe, Sam; Bodin, Roxana
Abstract : N/A: Transcatheter arterial chemoembolization (TACE) is a well‐recognized procedure for management of hepatocellular carcinoma. We present a 54‐year‐old man who presented with a periumbilical maculopapular skin rash that developed after an otherwise uneventful TACE procedure. A retrospective review of imaging was consistent with non‐target embolization of the hepatic falciform artery (HFA). He was treated with oral non‐steroidal anti‐inflammatory medication for 3 weeks with improvement, but had slight skin induration and an excoriated papule at 6‐month follow‐up. Non‐target embolization of HFA is very rare, but clinicians and interventionalists should be aware of this complication, especially in patients predisposed to enlargement of HFA.